Resolusi Konflik Keluarga Perspektif Teori Murray Bowen dan Jay Halley: Studi Kasus Masyarakat Sumatera Utara dengan adat “Dalian Na Tolu” - Muhammad Sholeh (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This study investigates the understanding of Islamic family law in urban communities in North Sumatra, focusing on the areas of Medan and its surroundings, Mandailing Natal, Padangsidimpuan, Sibolga, and Tarutung. A qualitative approach was used to gain an in-depth understanding of how factors such as education level, local culture, access to information, and religious influence affect this understanding. The results show variations in the understanding of Islamic family law in these areas, with a stronger understanding observed in Mandailing Natal, followed by Padangsidimpuan, Sibolga, and Tarutung. Factors such as active religious institutions and strong local cultures play a significant role in shaping people's understanding of Islamic family law. Case studies highlight several family conflict issues that often arise. The study also relates findings to the theories of Murray Bowen and Jay Halley, illustrating how the concept of "Dalian Na Tolu" in Batak Toba and Mandailing cultures can be an important instrument in resolving family conflicts. The implications and recommendations of this study emphasize the importance of education, access to information, the role of religious leaders, and government policies in improving understanding and resolving family conflicts based on Islamic law in urban communities in North Sumatra.